A study of some physical, chemical and biological properties of Slabiaat River waters in Al-Muthanna province, Iraq - Baghdad Science Journal (مجلة بغداد للعلوم, 2017)
Present study was conducted in order to assess Slabiaat water quality by measuring some physical and chemical factors of river water, the study included a choice of three stations along of Slabiaat River in Samawa city, water samples collected a monthly during the period from September 2013 August 2014. The study involved measuring the Air & water temperatures, pH, Electrical conductivity, Total dissolved solids, Dissolved oxygen, Total hardness, calcium hardness, magnesium, turbidity, and some types of bacteria in River water. The study results showed that the values of air & water temperatures have ranged between (20.1-36.6)?C , (10-21.8) in Slabiaat River, respectively . pH values ranged between (6.6-8.7). Electrical conductivity in study sites record values ranged between (2625-9775) µs? cm. Total dissolved solids showed values are changing through months of study and between stations was highest (5500 mg/L) in S3. Dissolved oxygen values ranged between (4-7 mg/L) in Slabiaat River. Total hardness, calcium and magnesium were (690-2100), (500-1020) and (12.15-325.62) mg CaCO3/L, respectively, either turbidity values were the highest value in the river is (98) NTU, and the lowest was (12) NTU. Also,It has been identified Staphylococcus, E. coli, Vibrio, Proteus & Pseudomonas in river waters. Statistically, significant differences have emerged in all physical and chemical characteristics between months at probability (P? 0.05), while did not show between stations, except for calcium hardness.